Fokker-Planck Equation for a Metastable Time Dependent Potential - Araujo, M. T. [UNESP]; Drigo Filho, E. [UNESP] (Springer, 2014)
We use the Fokker-Planck equation to study the diffusion process driven for a metastable potential within a temporal dependence. This potential is characterized by the existence of a barrier that increases with time and reduces the particle diffusion. Escape rate across the barrier for different values of diffusion coefficient is analyzed. The results are also associated with the diffusion process through ion channels in biological system.
Keywords: Fokker-Planck equation; Metastable potential; Time dependent process; Ion channel